Clinical practice guidelines for the surgical endodontic management of post-treatment periapical disease - Claudia C. García-Guerrero; Diana Carolina Lara-Rodríguez; Lina María García-Serrano (Universidad de Antioquia, 2019)
Introduction: in Colombia, persisting post-endodontic disease has been reported by up to 45%, validating the use of secondary alternative therapies, like endodontic microsurgery (EM). The aim of this study was to systematically-and with reliable scientific evidence-develop de Novo Clinical Practice Guidelines for the surgical endodontic management of post-treatment periapical disease (PPD), with more accurate recommendations for therapeutic decisions and preferences consulted with both practitioners and patients. Method: the guidelines developers team identified EM as a topic in the literature and established the scope, objective, questions, and outcomes, which were analyzed using the scientific evidence reported in secondary or primary clinical studies. A first screening identified titles and abstracts for each question asked. The validity of the selected studies was quantified with tools like AMSTAR or SIGN. Finally, the strength of recommendations and the quality of evidence were confirmed with GRADE. Results: concepts like PPD, EM indication, use of local anesthetics, antibiotics and presurgical anti-inflammatory drugs, effect of magnification, implementation of cone beam computed tomography, hemostasis, retrograde filling, and control time were integrated, supporting each topic with relevant evidence, experts' recommendations, and even good practice points. Conclusions: this document is considered a tool with sufficient evidence for clinical decision-making in EM.